Urgensi Penyelesaian Kasus Pelanggaran Hak Asasi Manusia Dimasa Lampau Perspektif Hukum Islam - Fredy Gandi Midhiya (Institut Agama Islam Negeri Metro, 2021)
Human rights are rights that have been possessed by every human being from birth that has been conferred from Alah. The first human rights were given by the Prophet Muhammad Saw in the teachings of Islam that every Friday exempting 1 slave and giving emancipation to the woman who was then told, as many as the new century of nations besides the country participated Apply human rights. There are many human rights that occur from the past and there are even the kasusu that is not revealed or reported to the authorities. This is detrimental to victims. The Government has proclaimed for human rights protection but still has been a violation. Efforts that have been made by the Government by making legislation in various chapters need cooperation with the parties.